Analisis SWOT dalam Program Humas Berupa Sosialisasi Penerimaan Siswa Baru di SMP ZIIS Cilongok - Ichwan Hero H; Umi Halwati Umi (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to analyze the education PR program in the form of socialization of new student admissions at ZIIS Cilongok Middle School using SWOT analysis. There is a problem that socialization is very difficult to run due to several things such as communication between implementing socialization activities. This research uses a case study approach and qualitative methods. The subject of this research is the Head of Lembaga pendidikan. Vice Head of Public Relations, Student Guardians and Teacher Council. Data collection techniques used interviews, observation and documentation. The analytical techniques used in this study were data condensation, data display, and conclusion drawing and verification. SWOT analysis is used as a basis that can be used for the analysis of Education Public Relations programs. In this study, the strengths (Strengths) in implementing the socialization program are: Good reputation. while the Weaknesses themselves are in the form of limited resources and lack of time. Next, opportunities are in the form of partnerships with other institutions. Meanwhile, the threats in carrying out this socialization program are competition with other schools and changes in education policy. Thus SWOT analysis becomes a very important ingredient in implementing a program so that later the program can run properly and correctly.